114. An unexpected target of Spinal Direct Current Stimulation: Interhemispheric connectivity in humans. Issue 4 (April 2016) - Vannini, B.; Bocci, T.; Caleo, M.; Vergari, M.; Rossi, S.; Priori, A.; Hensgens, M.J.M.; Sartucci, F.
Abstract : Transcutaneous spinal Direct Current Stimulation (tsDCS) is a noninvasive technique based on the application of weak currents over spinal cord. We studied the effects of tsDCS on interhemispheric connectivity and visual processing by evaluating changes in ipsilateral Silent Period (iSP), Transcallosal Conduction Time (TCT) and hemifield Visual Evoked Potentials (hVEPs), before and at different intervals following sham, anodal and cathodal tsDCS (T10–T12 level, 2.0 mA, 20 ′ ). Motor Evoked Potentials (MEPs) were recorded from abductor pollicis brevis (APB), abductor hallucis (AH) and deltoid muscles. hVEPs were recorded bilaterally by reversal of a horizontal square wave grating. Anodal tsDCS increased TCT ( p < 0.001) and the interhemispheric delay for both the main VEP components (N1: p = 0.0003; P1: p < 0.0001), dampening iSP duration (APB: p < 0.0001; AH: p = 0.0005; deltoid: p < 0.0001), while cathodal stimulation elicited opposite effects ( p < 0.0001). tsDCS would be a promising therapeutic tool in managing a number of human diseases characterized by an impaired interhemispheric processing, with anodal stimulation leading to a functional disconnection between hemispheres. It could also be helpful as an early rehabilitation strategy in patients with acute brain lesions, when other non-invasive brain stimulation techniques are not indicated due to safety concerns.